The Effect of Project Based Learning Model on Science Understanding and Process Skills of Renewable Energy Material - Zalentri, Ega; Purwanto, Andik; Desy Hanisa Putri (Jurnal Penelitian Pembelajaran Fisika, 2025)
In the Merdeka Curriculum, learning objectives include learning skills that students must achieve at each stage. The learning objectives in Phase E consist of elements of scientific understanding and process skills. This study aims to analyze the effect of the Project-Based Learning (PjBL) model on scientific understanding and process skills in renewable energy topics for 10th-grade students. The research employed a quasi-experimental method with a pretest-posttest non-equivalent control group design. The research instruments included multiple-choice tests to measure scientific understanding and observation sheets to assess process skills. The findings showed that the average posttest score of the experimental class was higher than that of the control class, and the Independent Samples t-test revealed a significant difference in scientific understanding. Students' process skills also showed significant improvement. The results indicate that students in the experimental class demonstrated better improvements in scientific understanding and process skills compared to those in the control class. In conclusion, the implementation of PjBL effectively enhances scientific understanding and process skills through an active and real-world problem-based learning approach.